Problem of Definition of Personal Security in the Modern Russian Criminal Procedure - ZAYTSEV, Oleg; GRINENKO, Aleksander; MAKEEVA, Inna; ZEINALOVA, Larisa; TASAKOV, Sergei; SLED, Yurii; EPIKHIN, Alexander; MISHIN, Andrei (Journal of Advanced Research in Law and Economics; Vol 7 No 6 (2016): Vol 7, No 6(2016): JARLE, Volume VII, Issue 6(20), Fall 2016, 2017)
The article represents comparison of various definitions and concepts related to the phenomenon of providing a secured protection of individuals participating in the Russian criminal procedure.
Keywords: individual, public protection, security, security of person, criminal procedure, criminal case, proceeding on a case, crime prevention, protection of witnesses, protection of victims